Preparation and Characterization of Cured Epoxy Resin with Hexachloro-Cyclo-Triphosphazene. Issue 2 (22nd January 2017) - Zarybnicka, Lucie; Bacovska, Radka; Spacek, Vladimir; Rychly, Jozef; Vecera, Miroslav; Alberti, Milan
ABSTRACT: Epoxy resins can exhibit some excellent properties. The basic principle of curing epoxy resins with a curing agent containing multiple amino groups is the crosslinking reaction between active hydrogen atoms from the curing agent and the oxirane groups in the epoxy resin structure. This study deals with the synthesis of derivative of hexachloro- cyclo -triphosphazene (HCCTP) using curing of epoxy resins. The study of our interest is nucleophilic substitution of HCCTP using N -[3-(trimethoxysilyl)propyl]ethylene diamine. The prepared derivative offers two potential advantages over conventional curing systems, namely improving properties during burning. GRAPHICAL ABSTRACT: